Ethnobotany of Medicinal Plants by the Pasean District Community in Pamekasan Regency as Components of Postpartum Herbal Remedies - Minarno, Eko Budi; Rahmah, Zainabur; Jannah, Sitti Hamsiyatul (El-Hayah:Jurnal Biologi, 2025)
The Madurese traditionally use medicinal plants to treat postpartum depression, which is a key time for both mother and child and a period of healing following childbirth. In order to properly document local wisdom, it is crucial to investigate the ethnobotany of postpartum medicinal herbs. Determining the kinds of postpartum herbal medicines, the medicinal plant types that comprise them, the plant organs, their applications, conservation strategies, and the phytochemical substances present in the remedies were the objectives of this study. This study is a descriptive exploratory investigation that employs interview and survey methods. The active ingredients in the herbal postpartum treatments were identified through phytochemical testing. .  The residents of West Dempo, East Dempo, and Tlontoraja Villages in Pasean District, Pamekasan Regency, served as the research sample. At Batu City's Herbal Materia Medica Laboratory, phytochemical analyses were carried out. Using 25 species of medicinal plants, the results revealed eight different forms of postpartum herbal remedies: 40-day herbal medicine, birth herbal medicine, lepcellep, parem, turmeric and tamarind, postpartum herbal medicine, pejje, and pilis. The leaf was the plant organ most frequently used (35%). Triterpenoids, tannins/phenols, alkaloids, and flavonoids were all present in the herbal postpartum treatments